2011
DOI: 10.1021/nn201224k
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation, Purification, and Unzipping of Carbon Nanotubes by Reaction with Molecular Hydrogen: Road to Graphane Nanoribbons

Abstract: Reaction of single-walled carbon nanotubes (SWNTs) with hydrogen gas was studied in a temperature interval of 400-550 °C and at hydrogen pressure of 50 bar. Hydrogenation of nanotubes was observed for samples treated at 400-450 °C with about 1/3 of carbon atoms forming covalent C-H bonds, whereas hydrogen treatment at higher temperatures (550 °C) occurs as an etching. Unzipping of some SWNTs into graphene nanoribbons is observed as a result of hydrogenation at 400-550 °C. Annealing in hydrogen gas at elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
78
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 48 publications
12
78
0
3
Order By: Relevance
“…2, where both (6,6)CNT-H0b and (5,5)CNT-H0b are transformed into a horseshoe shape. Since a (1) was calculated in terms of the total energy of the pure CNT E tot (CNT), the total energy of the H 2 molecule E tot (H 2 ), and the total energy of the hydrogenated CNT E tot (CNT + 2H). Table I shows E b obtained by using several exchangecorrelation functionals, in comparison to a previous work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2, where both (6,6)CNT-H0b and (5,5)CNT-H0b are transformed into a horseshoe shape. Since a (1) was calculated in terms of the total energy of the pure CNT E tot (CNT), the total energy of the H 2 molecule E tot (H 2 ), and the total energy of the hydrogenated CNT E tot (CNT + 2H). Table I shows E b obtained by using several exchangecorrelation functionals, in comparison to a previous work.…”
Section: Resultsmentioning
confidence: 99%
“…1 The density functional theory (DFT) calculations have in fact shown that hydrogen adsorption on CNTs may lead to transformation of the CNTs or transformation into a horseshoe shape. [2][3][4][5][6][7] The H-induced transformation of CNTs, which is considered as an origin of the coalescence of single-wall CNTs, 3,8 can be employed for production of well-characterized graphene nanoribbons 1 similarly to the case of oxygen-induced transformation of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Tylazin et al [25] have found that the reaction of SWCNTs with hydrogen gas at 550°C and at hydrogen pressure of 50 bar (5 MPa) can successfully remove all carbon coatings enclosing Fe particles in pristine samples. The H 2 -treatment temperature may be decreased at higher pressure to reduce the aggregation of Ag nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…83 Hydrogenation of CNTs also gives GNRs. 84 It was shown that hydrogenation at 400 ± 550 8C leads to opening of CNTs and formation of hydrogen-terminated GNRs. Yet another method 85 involves the oxidation of CNTs in a solution of PmPV in 1,2-dichloroethane.…”
Section: Graphene Nanoribbonsmentioning
confidence: 99%